The Use of Multiple Imaging Studies Before Shoulder Stabilization Surgery Is Increasing - Madeleine A. Salesky, B.A; Alan L. Zhang, M.D; C. Benjamin Ma, M.D; Brian T. Feeley, M.D; Valentina Pedoia, M.D; Drew A. Lansdown, M.D (Elsevier, 2022)
Purpose: To determine the incidence of preoperative shoulder imaging, explore the prevalence of obtaining multiple advanced imaging studies, and identify patient characteristics associated with specific imaging studies before anterior versus posterior shoulder stabilization surgery. Methods: The PearlDiver database was queried for patients who underwent anterior or posterior shoulder stabilization surgery from 2010 to 2019. The incidence of imaging studies within a year of surgery was collected. Patient characteristics were compared between groups using one-way analysis of variance or χ2 test. Results: In total, 10,252 patients underwent anterior shoulder stabilization surgery, and 1,108 patients underwent posterior shoulder stabilization surgery. Imaging use before anterior and posterior shoulder stabilization surgery included plain radiographs (69%, 70%, respectively), magnetic resonance imaging (MRI; 43%, 33%), and computed tomography (CT; 22%, 22%). In total, 1,098 patients (11%) received MRI and CT before anterior stabilization surgery and 85 patients (8%) received MRI and CT before posterior stabilization surgery. Over time, the incidence of obtaining MRI and CT increased before anterior (z = 2.54, P = .011) and posterior (z = 2.36, P = .018) stabilization surgery. Conclusions: This study highlights the increasing use of multiple imaging studies before shoulder stabilization surgery over recent years, including plain radiographs, MRI, and CT imaging. In total, 45% of anterior shoulder stabilization patients and 41% of posterior shoulder stabilization patients obtained more than 1 imaging study within a year of surgery, with a recent increase in patients obtaining both MR and CT scans preoperatively. Statement of Clinical Relevance: The increasing use of multiple preoperative imaging studies observed in this study highlights an opportunity for new imaging technology to streamline and improve the preoperative workup.